Genomic Analysis of Carbapenem-Resistant Acinetobacter baumannii Isolates Belonging to Major Endemic Clones in South America - Nodari, Carolina Silva; Cayô, Rodrigo; Streling, Ana Paula; Lei, Felipe; Wille, Julia; Almeida, Myriam S.; de Paula, Alexandre Inacio; Pignatari, Antonio Carlos Campos; Seifert, Harald; Higgins, Paul G.; Gales, Ana Cristina (Frontiers in Microbiology, 2020)
Carbapenem-resistant Acinetobacter baumannii (CRAB) are emerging worldwide. In South America, clinical isolates presenting such a phenotype usually do not belong to the globally distributed international clone 2 (IC2). The majority of these isolates are also resistant to multiple other antimicrobials and are often designated extremely drug-resistant (XDR). The aim of this study was to characterize the resistance mechanisms presented by 18 carbapenem-resistant A. baumannii isolates from five different Brazilian hospitals. Species identification was determined by rpoB sequencing, and antimicrobial susceptibility was determined by broth microdilution. Isolates were submitted to whole genome sequencing using Illumina platform and genetic similarity was determined by PFGE, MLST, and cgMLST. Genome analysis was used to identify intrinsic and acquired resistance determinants, including mutations in the AdeRSABC efflux system and in outer membrane proteins (OMPs). All isolates were identified as A. baumannii and grouped into 4 pulsotypes by PFGE, which belonged to clonal complexes (CC) 15Pas/103Ox (n=4) and 79Pas/113Ox (n=14), corresponding to IC4 and IC5, respectively. High MIC values to carbapenems, broad-spectrum cephalosporins, amikacin, and ciprofloxacin were observed in all isolates, while MICs of ampicillin/sulbactam, gentamicin, and tigecycline varied among the isolates. Minocycline was the most active antimicrobial agent tested. Moreover, 12 isolates (66.7%) were considered resistant to polymyxins. Besides intrinsic OXA-51 and ADC variants, all isolates harbored an acquired carbapenem-hydrolyzing class D β-lactamase (CHDL) encoding gene, either blaOXA-23 or blaOXA-72. A diversity of aminoglycoside modifying enzymes and resistance determinants to other antimicrobial classes were found, as well as mutations in gyrA and parC. Non-synonymous mutations have also been identified in the AdeRSABC efflux system and in most OMPs, but they were considered natural polymorphisms. Moreover, resistance to polymyxins among isolates belonging to IC5 were associated to non-synonymous mutations in pmrB, but no known polymyxin resistance mechanism was identified in isolates belonging to IC4. In conclusion, A. baumannii clinical isolates belonging to South America’s major clones present a myriad of antimicrobial resistance determinants. Special attention should be paid to natural polymorphisms observed in each clonal lineage, especially regarding non-synonymous mutations in constitutive genes associated with distinct resistance phenotypes.